Analysis of lipophilic fluorescent products in blood of Alzheimer's disease patients - Chmátalová, Zuzana; Vyhnálek, Martin; Laczó, Jan; Hort, Jakub; Skoumalová, Alice (Journal of cellular and molecular medicine, 2016)
Alzheimer's disease (AD) is a severe neurodegenerative disorder characterized by cognitive decline. Prodromal stage of AD, also called mild cognitive impairment (MCI), especially its amnestic type (aMCI), precedes dementia stage of AD. There are currently no reliable diagnostic biomarkers of AD in the blood. Alzheimer's disease is accompanied by increased oxidative stress in brain, which leads to oxidative damage and accumulation of free radical reaction end-products. In our study, specific products of lipid peroxidation in the blood of AD patients were studied. Lipophilic extracts of erythrocytes (AD dementia = 19, aMCI = 27, controls = 16) and plasma (AD dementia = 11, aMCI = 17, controls = 16) were analysed by fluorescence spectroscopy. The level of these products is significantly increased in erythrocytes and plasma of AD dementia and aMCI patients versus controls. We concluded that oxidative stress end-products are promising new biomarkers of AD, but further detailed characterisation of these products is needed.
Keywords: Male; blood; fluorescenční spektrometrie; biomarkers; Alzheimerova nemoc; Alzheimer Disease; oxidative stress; Aged; mužské pohlaví; senioři; Alzheimer's disease; lipofuscin-like pigments; senioři nad 80 let; lipidy; lidé; ženské pohlaví; Humans; Aged, 80 and over; erytrocyty; Erythrocytes; Lipids; Spectrometry, Fluorescence; Female; lidé středního věku; Middle Aged